Natural quinolone antimicrobial agents from Malaysian Rutaceous species - Mohd Hassan, Norazian; Zakaria, Muhamad; Md Taib, Nurhaya; Mohd Kamal, Laina Zarisa; Abdul Karim, Khairul Anuar (2010)
The overwhelming majority of naturally occurring quinoline alkaloids are anthranilate-derived alkaloids. Various quinoline alkaloids with diverse structural types have been isolated and most of these alkaloids are typical and unique to the Rutaceae plant family. Some of these alkaloids especially which possess 4-oxygenated and 2-substituted 4-quinolone structures have been demonstrated to have promising antimicrobial activity. Three Malaysian Rutaceous species have been investigated for their natural quinolone antimicrobial agents, namely Glycosmis pentaphylla (Retz.) DC., Ruta angustifolia (L.) Pers. and Lunasia amara Blanco. Bioassay-guided isolation facilitated by using bioautographic agar overlay assay against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 35213 and Candida albicans ATCC 90028 as the indicator microbes has led to the isolation of antimicrobial 4-quinozolone, identified as arborine, a 4-quinolone with the trivial name graveoline and a 2-quinolone namely lunidonine from G. pentaphylla, R. angustifolia and L. amara, respectively. These alkaloids possessed promising antimicrobial activity with the minimum inhibitory concentrations (MICs) ranged between 125 µg/ml and 250 µg/ml against the tested microbes. Arborine and graveoline showed synergistic antimicrobial effect when tested in combination with ampicillin against E. coli with FIC index of 0.38 for each combination. Because of some structural similarity of these alkaloids with that of 4-quinolone antimicrobial agents, the alkaloids are suggested to be the natural quinolone antimicrobial agents which have the same cellular target as the synthetic agents, which is the bacterial DNA. The study on DNA binding ability of these alkaloids is ongoing.